Looking Within: Intentions of Practice for Person-Centered Care - Ventres, William B. (Ann Fam Med, 2017)
In order to integrate the biological, psychological, social, and existential dimensions of care into my day-to-day clinical encounters with patients, I have worked to cultivate several intentions of practice. These intentions of practice—habits of mind that nurture my resolve to attend to patients as complex human beings— help me navigate my interactions with patients and families in ways that are simultaneously efficacious and therapeutic. When routinely recalled and adeptly implemented, they are what distinguish me as a competent and capable practitioner of person-centered care, when I am at my best, from when I am not. I present them here in hopes that others may find them useful as they progress down their ongoing paths as healing physicians.